The Relationship between Cognitive Learning Outcomes and Scientific Argumentation through Socio Scientific Issues Based Liveworksheets - Hudin, Yuni Afriani; Saefuddin, Saefuddin; Esnawi, Esnawi (The Future of Education Journal, 2026)
This study aims to determine the relationship between cognitive learning outcomes and scientific argumentation skills through the implementation of Socio-Scientific Issues (SSI)–based Liveworksheets on the topic of buffer solutions in Grade XII science classes at SMAN 2 Bungku. This research employed a correlational design using a survey method. The population consisted of all Grade XII science students at SMAN 2 Bungku, totaling 74 students, with a sample of 42 students selected through random sampling. Data on scientific argumentation skills were obtained through an essay test assessed using the Toulmin’s Argument Pattern (TAP) rubric, while data on cognitive learning outcomes were collected through a 20-item multiple-choice test. Data analysis was conducted using simple linear regression and Pearson’s product-moment correlation with the assistance of SPSS version 25. The results indicated that both variables were normally distributed and linearly related. The correlation coefficient (r) was 0.767 with a significance value of 0.000 < 0.05, indicating a positive and significant relationship between students’ scientific argumentation skills and their cognitive learning outcomes. The coefficient of determination (R²) was 0.637, meaning that 63.7% of the variance in cognitive learning outcomes was influenced by scientific argumentation skills, while the remaining 36.3% was affected by other factors beyond the scope of this study. Thus, it can be concluded that the higher the students’ scientific argumentation skills, the higher their cognitive learning outcomes. The implementation of SSI-based Liveworksheets was proven effective in enhancing students’ scientific argumentation skills and conceptual understanding of buffer solutions.